Pengaruh Harga dan Customer Review Terhadap Minat Beli Produk - Ganyang Tun Machmed; Wier Ritonga (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study describes the effect of price and customer review on the purchase intention of Teh Gelas products among Tokopedia users in Jakarta. With the object of research, one product from Teh Gelas is 300ml glass packaging. This study discusses the theory of 3 research variables, namely, price, customer review, and buying interest. This study uses a quantitative method by distributing questionnaires with Google Form to 122 respondents which is then processed using the SPSS version 13.0 program using a saturated sampling technique to take sample data. This study confirms that customer reviews significantly influence purchase intention, while the price is not a determining factor. The results of this study will help marketing pay serious attention to consumer reviews on online platforms. Therefore, various negative comments must be quickly responded to provide balanced information for potential buyers who tend to read previous buyer comments.